Investigation of temperature profile for liquefied petroleum gas storage operations - Zakaria, Zainal; Mustafa, Azeman (2005)

(untitled)
The investigation of temperature profile of liquefied petroleum gas during discharging process as the initial step in a usage management of LPG, which is an essential part to evaluate the left over problem. Experiments have been conducted to predict the evaporation behavior of LPG in portable cylinder with 50k water capacity. In a parallel effort, a computer model has been developed based on the unsteady state of heat transfer concepts using MATCAB 2000 to simulate the evaporation process in the LPG portable cylinder under various conditions taking account such as discharging flow rate and surrounding temperatures. The objective of this paper is a description of the LPG evaporation process and performance of calculation model to investigate the temperature profile. A rather good agreement between the theoretical and experimental data was obtained.